Fundamental Stock Assessment Using the Dividend Discount Model and Price Earning Ratio Method for Investment Decisions in the Banking Sector Listed on the Indonesian Stock Exchange (International Forum of Researchers and Lecturers, 2024)
This study was conducted to determine the fair value of shares of banking sector companies for the period 2022. We evaluated the stocks of five companies listed on the Indonesia Stock Exchange based on two approaches: the dividend discount model and the price-to-earnings ratio . The survey results of five companies show that two companies are undervalued and three companies are overvalued. If an investor is undervalued, he can decide to buy the stock, while an overvalued investor can sell the stock.